Presence and Role of the Type 3 Fimbria in the Adherence Capacity of Enterobacter Hormaechei Subsp. Hoffmannii - Fernandez-Yañez, V (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Enterobacter hormaechei, one of the species within the Enterobacter cloacae complex, is a relevant agent of healthcare-associated infections. In addition, it has gained relevance because isolates have shown the capacity to resist several antibiotics, particularly carbapenems. However, knowledge regarding colonization and virulence mechanisms of E. hormaechei has not progressed to the same extent as other Enterobacteriaceae species as Escherichia coli or Klebsiella pneumoniae. Here, we describe the presence and role of the type 3 fimbria, a chaperone-usher assembled fimbria, which was first described in Klebsiella spp., and which has been detected in other representatives of the Enterobacteriaceae family. Eight Chilean E. cloacae isolates were examined, and among them, four E. hormaechei isolates were found to produce the type 3 fimbria. These isolates were identified as E. hormaechei subsp. hoffmannii, one of the five subspecies known. A mutant E. hormaechei subsp. hoffmannii strain lacking the mrkA gene, encoding the major structural subunit, displayed a significantly reduced adherence capacity to a plastic surface and to Caco-2 cells, compared to the wild-type strain. This phenotype of reduced adherence capacity was not observed in the mutant strains complemented with the mrkA gene under the control of an inducible promoter. Therefore, these data suggest a role of the type 3 fimbria in the adherence capacity of E. hormaechei subsp. hoffmannii. A screening in E. hormaechei genomes contained in the NCBI RefSeq Assembly database indicated that the overall presence of the type 3 fimbria is uncommon (5.94–7.37%), although genes encoding the structure were detected in representatives of the five E. hormaechei subspecies. Exploration of complete genomes indicates that, in most of the cases, the mrkABCDF locus, encoding the type 3 fimbria, is located in plasmids. Furthermore, sequence types currently found in healthcare-associated infections were found to harbor genes encoding the type 3 fimbria, mainly ST145, ST78, ST118, ST168, ST66, ST93, and ST171. Thus, although the type 3 fimbria is not widespread among the species, it might be a determinant of fitness for a subset of E. hormaechei representatives. © 2024 by the authors.